Briquette Ratio Investigation of Charcoal Briquette Produced from Brick-Burning-Process Residual Charcoal - วิไลพล, ปฐมศก; เจริญสวรรค์, ปิยะนันท์; สีหะวงษ์, นพรัตน์; เม่นเกิด, จิรานุวัฒน์; ประกอบกสิกรณ์, ปรากรณ์; คำบุญ, ปิยะวัต (RMUTL Engineering Journal, 2019)
According to the survey of a SME brick factory, it was found that the brick burning process produces a large amount of charcoal residue. It seems that this kind of waste has high potential as the raw material for charcoal briquetting. In this study, the charcoal was mixed with water and starch. The compressed pressure was set to 5 MPa by using a universal testing machine. The percentage of charcoal : water : starch was varied between 42-51%, 41-51% and 2-14% respectively. The briquette burning test showed that 49:49:2% briquette has the shortest ignition and water boiling durations. In addition, the heating values of the briquettes were between 6726 cal/g.